Teoretyczna dokładność statystycznej metody reprezentacyjnej pomiaru miąższości obrębu leśnego - Jabłoński, Marek (Leśne Prace Badawcze, 2011)
In 2003, a new method of forest inventory based on stratified sampling was implemented in State Forests in Poland. In this paper, the results of analyses concerning the accuracy of growing stock assessment based on new method are presented. Firstly methods adopted in forest management planning for accuracy estimation are discussed. In the next step, the theoretical accuracy of inventory at the strata level as well as that of the forest division was calculated. For this purpose data from 12 forest districts (28 forest divisions) were used. Using formula from the literature standard errors and confidence intervals for these data were calculated. Stratification of stands is usually made based on data from Information Systems of the State Forests (updated old forest characteristics), while the results of the inventory are presented according to the new stand assessment method. The analysis of differences between updated and new data and their influence on the accuracy of growing stock assessments are presented in the paper.